Analysis Of Public Services In The Village Of Husein Sastranegara - Henni Zainal; Muhsin Efendi; Ade Risna Sari; Rusydi Fauzan; Didik Supriyanto (STIE AMKOP, 2023)
PA good service can satisfy its customers. Essentially, public services are operated by the government to suit the requirements of the community. One of them is public service in Husein Sastranegara Village. The goal of this paper is to investigate the analysis of public services in the village of Husein Sastranegara. As state officials, the basic task of the state apparatus is to serve. Citizens have the right to receive public services as well as the right to be protected. This analysis use the descriptive method. This analysis relies on secondary data sources, which include books, articles, journals, and other related sources. As a consequence of this examination, the service in Husein Sastranegara Village performs its obligations admirably. The officers have strong ethics, are kind and professional when serving the community, and the information supplied is clear and easy to grasp. Keywoard: PA, good service, customer satisfaction, public services, government, Husein Sastranegara Village, analysis, state officials